Tracking peripheral vascular function for six months in young adults following SARS‐CoV‐2 infection - Valesha M. Province; Rachel E. Szeghy; Nina L. Stute; Marc A. Augenreich; Christian E. Behrens; Jonathon L. Stickford; Abigail S. L. Stickford; Stephen M. Ratchford (Physiological Reports, 2022)
Abstract SARS‐CoV‐2 infection is known to instigate a range of physiologic perturbations, including vascular dysfunction. However, little work has concluded how long these effects may last, especially among young adults with mild symptoms. To determine potential recovery from acute vascular dysfunction in young adults (8 M/8F, 21 ± 1 yr, 23.5 ± 3.1 kg⋅m−2), we longitudinally tracked brachial artery flow‐mediated dilation (FMD) and reactive hyperemia (RH) in the arm and hyperemic response to passive limb movement (PLM) in the leg, with Doppler ultrasound, as well as circulating biomarkers of inflammation (interleukin‐6, C‐reactive protein), oxidative stress (thiobarbituric acid reactive substances, protein carbonyl), antioxidant capacity (superoxide dismutase), and nitric oxide bioavailability (nitrite) monthly for a 6‐month period post‐SARS‐CoV‐2 infection. FMD, as a marker of macrovascular function, improved from month 1 (3.06 ± 1.39%) to month 6 (6.60 ± 2.07%; p < 0.001). FMD/Shear improved from month one (0.10 ± 0.06 AU) to month six (0.18 ± 0.70 AU; p = 0.002). RH in the arm and PLM in the leg, as markers of microvascular function, did not change during the 6 months (p > 0.05). Circulating markers of inflammation, oxidative stress, antioxidant capacity, and nitric oxide bioavailability did not change during the 6 months (p > 0.05). Together, these results suggest some improvements in macrovascular, but not microvascular function, over 6 months following SARS‐CoV‐2 infection. The data also suggest persistent ramifications for cardiovascular health among those recovering from mild illness and among young, otherwise healthy adults with SARS‐CoV‐2.